Legal Consequences Of Canceling The Agreement Unilaterally - Totok Leksono; Mohammad Albar (Journal of Law Science, 2024)
Termination of an agreement unilaterally can be sued with a lawsuit for violating the law, because unilateral cancellation is an action that is not justified if it is not based on clear reasons according to the agreement and this of course violates the legal obligations of each party, namely to always act in good faith. , act in accordance with propriety, prudence, and do not conflict with the law. Legal research has the aim of finding a way out of a particular problem related to legal issues. The legal research used is normative legal research or doctrinal legal research. Cancellation of an agreement will definitely have legal consequences for the parties entering into the agreement. The consequences of canceling the agreement are regulated in Article 1451 of the Civil Code and Article 1452 of the Civil Code. Cancellation of the agreement results in a return to the original position as before the agreement was made by both parties. Unilateral termination of the agreement is an unlawful act. For these unlawful acts, a person can file a lawsuit for unlawful acts to ask for compensation, either in the form of material or immaterial compensation for the actions of one of the parties who cancel the agreement unilaterally.